(untitled) (Al-Academy, 2017)
It is doubtless that the sexual place has some common indicators due to the masculine and feminine bodies which may be natural or deviated (homosexual). The female has an act of voice in the imaginary masculine place whereas the male has an act of image recognized in the parental mind in both the secular and sacred place. Those places create different limits and perceptions according to the auditory and visual readings in search of identity, text and body in the feminine dramatic text. The research includes four chapters; the first, the methodological framework, involves the problem which is centralized in the following enquiry: What is the relationship between the place and the term of sexuality and its nature in the text of the lover and the beloved dramatically? The importance of the research is that it is a comprehensive, sociological, and cultural study which reveals the theme of feminine text and the relationship between the place and the term of sexuality. Consequently it focuses on the female, her troubles, and her relationship with a society that seeks the physical cultural and biological relationships. The aim of the research is to identify the sexual place in the text of the lover and the beloved dramatically. The limits of the research are restricted to the play (The Lover and the Beloved) by the Omani female writer (Amina Al-Rabee’) in (2008). The chapter is finalized by the definition of the basic terms of the title. The second chapter, the theoretical framework, involves two sections, the first deals with the sexuality of the place and character whereas the second is concerned with studying the sexuality of the place in the text literally and dramatically. The chapter ends with the indicators which the theoretical framework has come up with. The third chapter includes the procedures which are the society, the sample, the tool. The methodology, and the analysis. The fourth chapter contains the results, the most important of which are: The secular place has no special or meaningful indication depending on the celebratory, homosexual relationships which consider the body a resort of seductions and deceptions to link the self with the other or the lover with the beloved. The relationship of the place with the feminine body has an actual, sensed entity to which the bodies resort and which the sexual indicators connect due to the par psychological power The chapter also involves the conclusions and the bibliography.